AKSENTUASI NILAI-NILAI ILAHIYAH DALAM PANDEMI COVID-19 - Robingun Suyud El-Syam; Rifqi Muntaqo (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2021)
This article aims to analyze the accentuation of Divine values ​​in the Covid-19 pandemic. This study uses a qualitative research library study, while the research approach is socio-historical. The results of the study explain where the Divine values ​​in Covid-19 (which are divided into three kinds of core values, including the values ​​of faith, the values ​​of trust and the values ​​of patience) are important to be transformed for students to believe in and practice in everyday life during this pandemic. And several hadiths of the Prophet also strengthen the existence of efforts to deal with epidemics that occurred in ancient times.